Deconstructing the tourist’s (colonizer’s) gaze in a small place - BAKIR, CAHİT (My University, 2017)
This article explores how, inA Small Place, Jamaica Kincaid opens the colonial history of Antigua to negotiation through a constantly changing gaze in order to deconstruct the colonial and neo-colonial hegemony on the island. By incorporating the issue of \"gaze\" into the discourse of colonialism and reversing the privileged position the white western supremacists have held over the colonized subjects, Kincaid obliges the American or European tourist to focalize the colonial discourse through the eyes of the oppressed and exploited subjects. However, while subverting the superiority of the white western tourist whose presence on the island stands for the representation of the colonial heritage, Kincaid describes both Antigua and Native Antiguans, both of whom are constructed in relation to England and English colonizers respectively, as an image, a construction of the white man rather than a land and people with a distinct history. Thus, by focusing on shifting viewpoints, the constant change in tone and voice as well as the various levels of narrative elements throughout the text, this study aims to explore how Kincaid first deconstructs and then redefines the colonial history and identity from an anti-establishment perspective in A Small Place.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Batı Dilleri ve Edebiyatları; İngiliz Dili ve Edebiyatı; Social Sciences and Humanities; Philology; Western Languages and Literatures; English Language and Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT, ALMAN, HOLLANDA, İSKANDİNAV; EDEBİYAT, İNGİLİZ ADALARI; EDEBİYAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE, GERMAN, DUTCH, SCANDINAVIAN; LITERATURE, BRITISH ISLES; LITERATURE; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities; colonial and neo-colonial hegemony; gaze; colonial discourse; shifting viewpoints; narrative elements